2010
DOI: 10.1186/1471-2202-11-148
|View full text |Cite
|
Sign up to set email alerts
|

Long descending cervical propriospinal neurons differ from thoracic propriospinal neurons in response to low thoracic spinal injury

Abstract: BackgroundPropriospinal neurons, with axonal projections intrinsic to the spinal cord, have shown a greater regenerative response than supraspinal neurons after axotomy due to spinal cord injury (SCI). Our previous work focused on the response of axotomized short thoracic propriospinal (TPS) neurons following a low thoracic SCI (T9 spinal transection or moderate spinal contusion injury) in the rat. The present investigation analyzes the intrinsic response of cervical propriospinal neurons having long descendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 82 publications
7
42
0
Order By: Relevance
“…Further, the upregulation in LVN neurons was more prolonged than in propriospinal neurons. Interestingly, Siebert et al (2010b) show that gene expression in long propriospinal neurons injured in the same experiment showed a more typical downregulation of genes related to regeneration and less cell death, supporting the idea that a critical factor in the regenerative response may be the distance from the injury to the cell body (Fernandes et al, 1999;Mason et al, 2003a;Siebert et al, 2010b).…”
Section: Regeneration-related Genesmentioning
confidence: 57%
“…Further, the upregulation in LVN neurons was more prolonged than in propriospinal neurons. Interestingly, Siebert et al (2010b) show that gene expression in long propriospinal neurons injured in the same experiment showed a more typical downregulation of genes related to regeneration and less cell death, supporting the idea that a critical factor in the regenerative response may be the distance from the injury to the cell body (Fernandes et al, 1999;Mason et al, 2003a;Siebert et al, 2010b).…”
Section: Regeneration-related Genesmentioning
confidence: 57%
“…This may suggest a different response to incision in some large-diameter neurons, with one response signified by short-term ATF3 expression without GAP-43, and another by sustained ATF3 and GAP-43 expression. There is precedent for different ATF3 expression patterns in different cells in the same condition (Ohba et al, 2003; Hai et al, 2010; Siebert et al, 2010; Yin et al, 2010). This may be impactful for post-incision sensation because different types of sensory neurons drive different aspects of sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…A bilateral distribution of retrograde-labeled propriospinal neurons within the spinal cord was observed, with a significantly higher occurrence of labeled cells on the ipsilateral side were reported in both PN nerve graft and isolated SCs graft models (Decherchi and Gauthier, 2000; Iannotti et al, 2003). However, due to the fact that intrinsic spinal cord neurons, especially long projecting propriospinal neurons, have various projection patterns including projection distance, laterality, or branching within the graft (Saywell et al, 2011; Siebert et al, 2010; Tuszynski and Steward, 2012; Verburgh and Kuypers, 1987), analysis of the size, distribution, and cytological features failed to yield specific identification of usual destinations of these labeled neurons. In addition to the anatomical differences,Siebert et al (2010) observed phenotypic variation in the post-injury response to axotomy between ldPST neurons and sdPST neurons.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the fact that intrinsic spinal cord neurons, especially long projecting propriospinal neurons, have various projection patterns including projection distance, laterality, or branching within the graft (Saywell et al, 2011; Siebert et al, 2010; Tuszynski and Steward, 2012; Verburgh and Kuypers, 1987), analysis of the size, distribution, and cytological features failed to yield specific identification of usual destinations of these labeled neurons. In addition to the anatomical differences,Siebert et al (2010) observed phenotypic variation in the post-injury response to axotomy between ldPST neurons and sdPST neurons. The ldPST neurons lacked both cell death and regenerative responses, and down-regulated many genes important for regrowth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation